2019
DOI: 10.1039/c8sc03816c
|View full text |Cite
|
Sign up to set email alerts
|

Three to tango requires a site-specific substitution: heterotrimetallic molecular precursors for high-voltage rechargeable batteries

Abstract: A site-specific substitution within the heterobimetallic LiMn2(thd)5 molecule allows for the design of the “true” heterotrimetallic LiMnCo(thd)5 precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Recent progress has revealed the trimetallic SSP LiMnCo(thd)5, whose trimetallic structure can be confirmed in the gas phase by Direct Analysis in Real Time (DART) mass spectrometry, and can be used to make LiMnCoO4. 113 The Dikarev group have also recently turned their attention to Na analogues, [NaM(tbaoac)3]2, of these SSPs, targeting cathodes for Na-ion battery technologies. 114 Oxalate anions, [C2O4] 2− , have been used to form many 2D or 3D coordination networks which may incorporate secondary metals as counterions, e.g.…”
Section: Mixed-metal Complexes With Other O-donor Ligandsmentioning
confidence: 99%
“…Recent progress has revealed the trimetallic SSP LiMnCo(thd)5, whose trimetallic structure can be confirmed in the gas phase by Direct Analysis in Real Time (DART) mass spectrometry, and can be used to make LiMnCoO4. 113 The Dikarev group have also recently turned their attention to Na analogues, [NaM(tbaoac)3]2, of these SSPs, targeting cathodes for Na-ion battery technologies. 114 Oxalate anions, [C2O4] 2− , have been used to form many 2D or 3D coordination networks which may incorporate secondary metals as counterions, e.g.…”
Section: Mixed-metal Complexes With Other O-donor Ligandsmentioning
confidence: 99%
“…66 The sub-surface enlarged region II′ and corresponding electron diffraction pattern in LRNCM show a lattice fringe of 0.24 nm, which is indexed to the (311) plane of a spinel structure (space group: Fd 3̄ m ). 67,68 These reveal that the outer surface and subsurface regions of LRNCM suffer from severe structural degradation and phase transformation during deep charge and discharge cycles. Consequently, it can be concluded that a stable surface protective layer is of great significance to avoid direct contact between the electrode and the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…DART Mass Spectrometry Investigation of Heterotrimetallic Complex 3. Direct Analysis in Real Time (DART) mass spectrometry has been successfully utilized to confirm the composition of complex heterometallic ions through their isotope distribution patterns 27,42,48 as well as to analyze the oxidation states of constituent transition metals. 49 In the positive-mode mass spectrum of solid [Mn(ptac) 3 NaFe-(acac) 3 NaMn(ptac) 3 ] (3), the peak corresponding to the [M-L] + (L = ptac; meas/calcd m/z = 1484.2365/1484.2410) ion appears with a characteristic isotope distribution pattern in good agreement with the simulated one (Figure 5a and SI, Figure S15 and Tables S17 and S18) confirming the presence S13−S16).…”
Section: ■ Results and Discussionmentioning
confidence: 99%